Polar Phonon Behaviour in Polycrystalline Bi-Doped Strontium Titanate Thin Films - Alexander Tkach (MDPI AG, 2021)
Strontium titanate-based materials with ferroelectric or relaxor-like properties have drawn vast attention as polar dielectrics for electronics and telecommunications. Here, we study the lattice dynamics in sol–gel-derived Sr1−1.5xBixTiO3 thin films with x = 0.0053 and 0.167, deposited on Al2O3 substrates, using a variable-temperature far-infrared spectroscopy in a transmittance mode. Bi doping, known to induce a low-frequency dielectric relaxation in SrTiO3 (ST) ceramics and films, due to off-centre dopant ion displacements generating electric dipoles, is shown to affect the polar phonon behaviour of thin films. We show that in weakly Bi-doped films, the low-frequency polar TO1 mode softens on cooling but less than in undoped ST. In heavily Bi-doped ST films, this mode displays no significant frequency variation with temperature from 300 to 10 K. The polar phonon behaviour of polycrystalline Bi-doped ST thin films is comparable with that of Bi-doped ST ceramics, which exhibit dielectric relaxations and harden soft-mode behaviour instead of the ferroelectric phase transition.